Media use as a predictor of young adult religiosity in the context of their identity styles and parental religiosity - Kutt, Marzena; Lelek-Kratiuk, Marzena (Kwartalnik Naukowy Fides et Ratio, 2021)
The article analyzes the relationship of press and Internet use by young adults or, according to Arnett’s approach, those entering adulthood, with their level of religiosity. The context for the correlation studied was the identity styles of the subjects and the religiosity of their parents, or rather the subjects’ perceived level of this religiosity expressed as a score on the Huber C-15 Scale. Religiosity can be characterized as a multidimensional structure that includes five representative, common, and relatively autonomous dimensions: experiential, ritualistic, ideological, intellectual, and consequential of religiosity. Young adults often represent a synthetic-conventional faith, which is strongly associated with authority figures and community. At this stage, religiosity is not yet fully internalized, so it fluctuates easily. The greatest influence on the level of religiosity seems to be the parents’ religiosity. At the same time, people representing the discussed age group are among the most engaged users of new media, which may also impinge on their faith. Polish studies proved that containing criticism of the Church and exposing its flaws may have a negative impact on the religiosity of the recipients. The study was conducted using a questionnaire prepared by M. Kutt and tools that have an established position in research practice (Berzonky’s Identity Styles Questionnaire and the C-15 Huber Scale). There is a correlations between specific identity styles, perceived religiosity of parents, frequency of media use, interest in specific topics and the level of religiosity of the subjects. Some of the formulated hypotheses were not positively verified. Conclusions: The most important variables explaining the level of religiosity of young adults turned out to be mother’s religiosity and normative style (positive correlation), as well as diffusion-union style (negative correlation). The negative correlation between the level of religiosity and interest in current information from the press as well as the Internet seems interesting.